2012
DOI: 10.1073/pnas.1207326109
|View full text |Cite
|
Sign up to set email alerts
|

Roles of cell confluency and fluid shear in 3-dimensional intracellular forces in endothelial cells

Abstract: We use a novel 3D inter-/intracellular force microscopy technique based on 3D traction force microscopy to measure the cell-cell junctional and intracellular tensions in subconfluent and confluent vascular endothelial cell (EC) monolayers under static and shear flow conditions. We found that z-direction cell-cell junctional tensions are higher in confluent EC monolayers than those in subconfluent ECs, which cannot be revealed in the previous 2D methods. Under static conditions, subconfluent cells are under spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 42 publications
(67 reference statements)
9
135
1
Order By: Relevance
“…Assuming the adhesions occupy 5% of the surface, the forces from adhesions spread over the whole cell would be 250 Pa. Traction forces that originate in myosin are therefore ,100 times larger than the forces from moderate physiological shear stress on the cell.] A more recent report determined that the forces within the cytoskeleton that are induced by exposing ECs to long-term shear stress were nearly one order of magnitude larger than the value required to passively balance the force from shear stress (Hur et al, 2012). Taken together, these observations suggest that the response of ECs to shear stress cannot be explained as a passive response to applied force (e.g.…”
Section: Mechanosensors Of Endothelial Shear Stressmentioning
confidence: 49%
“…Assuming the adhesions occupy 5% of the surface, the forces from adhesions spread over the whole cell would be 250 Pa. Traction forces that originate in myosin are therefore ,100 times larger than the forces from moderate physiological shear stress on the cell.] A more recent report determined that the forces within the cytoskeleton that are induced by exposing ECs to long-term shear stress were nearly one order of magnitude larger than the value required to passively balance the force from shear stress (Hur et al, 2012). Taken together, these observations suggest that the response of ECs to shear stress cannot be explained as a passive response to applied force (e.g.…”
Section: Mechanosensors Of Endothelial Shear Stressmentioning
confidence: 49%
“…VEGFR-2 in turn becomes tyrosine phosphorylated and activates downstream signaling events including the activation of AKT kinases (13,16). Biophysical evidence indicated that PECAM-1 is not a primary mechanosensor, but that it is controlled by upstream mechanisms that have remained elusive (17,18). Other mechanotransducers suggested to date include mechanosensitive ion channels (19)(20)(21), the endothelial glycocalyx layer (22,23), and the primary cilium (24).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that hypertension, diabetes and hypercholesterolemia promote atherosclerosis by disrupting the ability of the endothelium to respond to shear stress [1][2][3][4][5][6][7][8][9]. Therefore, elucidation of the mechanisms of shear-mediated signal transduction will greatly advance our understanding of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Responses of endothelial cells (ECs) to haemodynamic forces play a significant role in vascular health and disease [4][5][6][7][8][9]. It is well known that ECs transduce the fluid shear stress (FSS) resulting from blood flow into intracellular signals that affect gene expression and cellular functions such as proliferation, apoptosis, migration, permeability, cell alignment and mechanical properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The activation of signalling pathways by shear forces arises at discrete locations in ECs by force amplification and forceinduced directional biasing of signal propagation [1][2][3][4][10][11][12][16][17][18][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%